Partnerships in Mobile Financial Services : Factors for Success - Flaming, Mark; Mitha, Aiaze; Hanouch, Michel; Zetterli, Peter; Bull, Greta (International Finance Corporation, Washington, DC, 2015)
This paper is organized as follows: section one briefly presents the structure of MFS implementations and in particular the four key roles which must be fulfilled. Section two describes the case study implementations and the partnership arrangements between the key actors. Section three describes the importance of aligning competitive forces, economic motivation and partner roles. Section four presents key lessons related to the four underlying businesses of an MFS implementation, distinguishing between the direct and indirect revenue that can accrue to the core businesses of the partner organizations. It also presents key lessons related to the distribution of this revenue between partners.